2016
DOI: 10.2217/nnm-2016-0165
|View full text |Cite
|
Sign up to set email alerts
|

Surviving nebulization-induced Stress: Dexamethasone in pH-sensitive Archaeosomes

Abstract: DP-ApH suppressed IL-6 and TNF-α on phagocytic cells. Nebulized after 6-month storage, LpH increased size and completely lost its HPTS while ApH3 conserved size and polydispersity, fully retaining its original HPTS content.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 60 publications
0
27
0
Order By: Relevance
“…Opposingly, no differences in swelling diameter were observed between LIPO-IMQ+TLA and LIPO+IMQ+TLA. The low IMQ/PL ratio, much less extensive endocytic uptake of LIPO compared to ARC (Altube et al, 2016 ), together with the almost absent capacity of stimulating TNF-α and IL-6 on J774A.1 macrophages that rendered a less pronounced DTH on the other hand, suggested that only ARC but not LIPO, would succeed in modifying IMQ pharmacodynamics on target cells. Despite of not all immunogens inducing DTH are associated to a protective cell response (Nichols et al, 2002 ), a classical DTH reaction is considered indicative of cellular protective response (Crowle, 1975 ), mediated by T helper 1 (Th1) cells or activated CD4+ T cells (Cher and Mosmann, 1987 ) and CD8+ cytotoxic T cells (Kalish and Askenase, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Opposingly, no differences in swelling diameter were observed between LIPO-IMQ+TLA and LIPO+IMQ+TLA. The low IMQ/PL ratio, much less extensive endocytic uptake of LIPO compared to ARC (Altube et al, 2016 ), together with the almost absent capacity of stimulating TNF-α and IL-6 on J774A.1 macrophages that rendered a less pronounced DTH on the other hand, suggested that only ARC but not LIPO, would succeed in modifying IMQ pharmacodynamics on target cells. Despite of not all immunogens inducing DTH are associated to a protective cell response (Nichols et al, 2002 ), a classical DTH reaction is considered indicative of cellular protective response (Crowle, 1975 ), mediated by T helper 1 (Th1) cells or activated CD4+ T cells (Cher and Mosmann, 1987 ) and CD8+ cytotoxic T cells (Kalish and Askenase, 1999 ).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the polar archaeolipids extracted from Halorubrum tebenquichense , were identified by ESI-MS by Higa et al ( 2012 ) and ordered according to decrescent abundance as: archaeol analog methyl ester of phosphatidylglycerophosphate (PGPMe), archaeol analog phosphatidylglycerol (PG), (1-O-[α-D-mannose-(2′-SO3H)-(1′ α 2′)-α-D-glucose]-2,3-di-O-phytanyl-sn-glycerol) (SDGD5) the cardiolipin bis phosphatidylglycerol (BPG) and the glycocardiolipin SDGD5PA (2′-SO3H)-Manp-α1,2Glcpα-1-1-[sn-2,3-di-Ophytanylglycerol]-6-[phospho-sn-2,3-di-O-phytanylglycerol]. Recently the double negatively charged PGPMe, majoritarian polar lipid in H. tebenquichense responsible for its high negative Z potential of −40 mV, was confirmed to be a ligand of SRA-1 and not of SRB (the phosphatidylcholine receptor) (Altube et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the ether linkages of archaeolipids, ARC are resistant to hydrolysis; the fully saturated isoprenoid chains of archaeolipids make ARC resistant to oxidation and the sn 2,3 stereoisomery of archaeolipids makes ARC resistant to stereospecific phospholipases [48]. Besides, the double negatively charged PGP-Me, majoritarian polar lipid of H. tebenquichense, responsible for the ARC high negative zeta potential (-40 mV), is a ligand of SRA1 [21]. SRA1 is a scavenger receptor expressed mainly in macrophages and dendritic cells [49][50][51], with broad ligand binding properties [52].…”
Section: Discussionmentioning
confidence: 99%
“…Archaebacterias on the other hand, are known to possesses archaeolipids, lipids having unique chemical nature made of saturated isoprenoid chains linked via ether bonds to the glycerol carbons at the sn 2,3 position. Different to liposomes prepared with phospholipids from plants or animal sources, ARC are colloidal and chemically resistant to different stress such as heat sterilization, storage under cold-free conditions [20] and nebulization [21]. Importantly, ARC are stable under GI conditions and efficiently protect encapsulated proteins from digestion [22]; concomitantly, shells made of archaeolipids layer protect solid lipid nanoparticles from lipolysis [23].…”
Section: Introductionmentioning
confidence: 99%